PEMANFAATAN PEKTIN KULIT NANGKA (ARTOCARPUS HETEROPHYLLUS) SEBAGAI ADSORBEN LOGAM CU (II) - Khusnul Khotima; Tri Santoso (Universitas Tadulako, 2020)
One method to reduce levels of heavy metals from the waters is adsorption method by utilizing organic waste such as jackfruit peels. This research aims to utilize jackfruit peels pectin (Artocarpus Heterophyllus) as Cu (II) metal adsorbent the first to extract with 5% citric acid solvent for 120 minutes and characterize pectin from jackfruit peels as well measure the optimum contact time required pectin to adsorb Cu (II) metal with variations in time for 1, 2, 3 hours. The results showed the characterization pectin from jackfruit peels obtained was a yield of 9.9%, ash content 4.04%, moisture content 8%, equivalent weight 641.026 mg, methoxyl content 6.82%, galacturonic acid 45.76%, and the optimum contact time required pectin to adsorb Cu (II) metal, which is 2 hours with the precentage of absorption is 82,80%.